Viologen-bridged polyaniline based multifunctional heterofilms for all-solid-state supercapacitors and memory devices. (January 2018) - Wang, Luxin; Sun, Sai; He, Yafei; He, Nan; Zhang, Fan; Yao, Yefeng; Zhang, Bin; Zhuang, Xiaodong; Chen, Yu
Graphical abstract: The VBP|Au|VBP–based memory device and supercapacitor exhibited bistable non-volatile rewritable memory behavior with high ON/OFF current ratio of more than 10 5 and high volumetric capacitances up to 6.22 Fcm −3, respectively. Highlights: A novel viologen-bridged PANI film was synthesized through one-step electropolymerization. The in-situ synthesized Au NPs were sandwiched between VBP films to produce VBP|Au|VBP heterofilms. VBP|Au|VBP -based device exhibited a typical nonvolatile rewritable memory performance. VBP|Au|VBP -based super-capacitors exhibited a high volumetric capacitance of 6.22 F cm −3 . Abstract: Both the viologen and polyaniline (PANI) have shown high electrochemical redox activity that can be used to fabricate optoelectronic, electronic and energy storage devices as well as sensors. However, it still remains great challenge for integrating these two fascinating materials together via covalent linkage to avoid phase separation in physical mixtures. In this work, a novel viologen-bridged polyaniline film (hereafter called as VBP) onto the indium-tin-oxide (ITO) glass was prepared by one-step electropolymerization approach, and then the in-situ synthesized golden nanoparticles (AuNPs) were sandwiched between the VBP films to produce the heterofilms (VBP|Au|VBP) as active materials. The VBP|Au|VBP-based electronic memory device and all-solid-state supercapacitor, which exhibited bistable nonvolatile rewritable memory performance with high ON/OFF current ratio of 10 5 and high volumetric capacitance up to 6.22 Fcm −3, respectively, were fabricated through simple layer-by-layer method. This work not only offers a new and easy strategy for synthesizing viologen-bridged PANI materials through covalent bonding, but also paves the way for the development of high-efficient sandwich-type resistive random access memory (RRAM) devices and the all-solid-state supercapacitors based on rational designed heterofilms.